Genetic diversity of Anaplasma marginale in beef cattle in the Brazilian Pantanal - de Souza Ramos, Inalda Angélica [UNESP]; Herrera, Heitor Miraglia; Fernandes, Simone de Jesus [UNESP]; do Amaral, Renan Bressianini [UNESP]; Zanatto, Diego Carlos de Souza [UNESP]; da Silva, Thiago Merighi Viera [UNESP]; Horta, Bruna Le Senechal [UNESP]; Campos, João Bosco Vilela; Alves, João Vitor Almeida; de Macedo, Gabriel Carvalho; Machado, Rosangela Zacarias [UNESP]; André, Marcos Rogério [UNESP] (Elsevier, 2019)
There are few studies on the genetic diversity of Anaplasma marginale in Brazilian cattle herds, especially about beef cattle. The objective of this study was to evaluate the genetic diversity of A. marginale, based on the msp1α gene in Bos taurus indicus sampled from the Brazilian Pantanal. Aliquots of blood with and without EDTA were taken from 400 cattle (200 cows and 200 calves) across five extensive farms. The samples were submitted to the indirect immunoenzymatic assay (iELISA), quantitative real-time PCR (qPCR) for the msp1β gene and to the semi-nested (sn) PCR for the msp1α gene. Positive samples were sequenced by the Sanger method and subjected to diversity analysis using the RepeatAnalyser software. The percentage of positive animals by iELISA, qPCR and (sn) PCR was 72.2% (289/400), 56.7% (227/400) and 23% (52/227), respectively. Cows (154/200) showed to be significantly more seropositive than calves (135/200). In qPCR, the number of calves and average quantification value (138/200; 1.3 × 106) A. marginale msp1α copies per μL proved to be higher when compared to that found for the cows (89/200; 3.9 × 104). The microsatellite analysis of the 26 sequences obtained from the msp1α gene revealed the presence of E (77%), C (15.4%) and B (7.7%) genotypes. Fourteen A. marginale strains were identified in the studied region, with eight that have never before been described in the literature (τ-10-13−13-18; τ-27-18; EV8-EV8-17; α-β-β-β-100; EV7-11−10-15; τ-11-11−27-18; τ-11-10-15; τ-27-13-18). Beef cattle are highly exposed to A. marginale in the Brazilian Pantanal. Moreover, a high genetic diversity of A. marginale, with eight new strains, was found in the studied region. While cows may act as chronic carriers, perpetuating the pathogen within the herd, male beef calves sold to other regions may disperse these strains.
Keywords: Bos taurus indicus; Bovine anaplasmosis; Brazil; msp1α; Tandem repeats